2004
DOI: 10.1002/adma.200305660
|View full text |Cite
|
Sign up to set email alerts
|

Porous Tin Oxides Prepared Using an Anodic Oxidation Process

Abstract: Elucidating the properties of the interface between traditional inorganic solid-state conductors and novel organic COMMUNICATIONS 240

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
141
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(152 citation statements)
references
References 19 publications
9
141
1
1
Order By: Relevance
“…2(a) shows the results from the 1, 20, 100, and 300 μm-thick tin coatings on silicon, as well as the anodic tin oxide created from the tin foil. Only tin signals were observed in the anodic tin oxide from the tin foil (pattern E in the figure), in good agreement with the results of existing studies in that the anodic tin oxide formed on this substrate was confirmed as amorphous [1,17,18]. On the other hand, SnO 2 (200) signals of a tetragonal rutile structure were clearly observed for the anodic tin oxides obtained from the 20 and 100 μm-thick tin coatings on silicon.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…2(a) shows the results from the 1, 20, 100, and 300 μm-thick tin coatings on silicon, as well as the anodic tin oxide created from the tin foil. Only tin signals were observed in the anodic tin oxide from the tin foil (pattern E in the figure), in good agreement with the results of existing studies in that the anodic tin oxide formed on this substrate was confirmed as amorphous [1,17,18]. On the other hand, SnO 2 (200) signals of a tetragonal rutile structure were clearly observed for the anodic tin oxides obtained from the 20 and 100 μm-thick tin coatings on silicon.…”
Section: Resultssupporting
confidence: 79%
“…The tin oxide nanoporous structure was found to be well developed for both the tin foil and the silicon substrate. According to a previous study [1,17,18], anodic tin oxide created from a tin foil is usually amorphous or has a low degree of crystallinity. In this regard, the transmission electron micrograph and electron diffraction pattern of the anodic tin oxide formed on the silicon substrate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, spatially irregular porous structures are often observed during the anodization of aluminum [3], titanium [13] and tin [14]. However, in order to explain the formation of spatially regular, hexagonal arrays of pores, some additional mechanism is needed that would produce a short-wave instability.…”
mentioning
confidence: 99%
“…As the applied voltage to the anode is increased, the thickness of this barrier layer will in turn linearly increase with the voltage [1, ch.6]. In certain metals, such as aluminum [2,3], titanium [4,5,6], zirconium [7], niobium [8], tantalum [9], tungsten [10] and tin [11], the surface of the barrier layer can become unstable, causing pores to form in the oxide. These nanostructured materials have found applications in many areas such as catalysts, gas sensors and coatings for batteries.…”
Section: Introductionmentioning
confidence: 99%